KARYA SINEMATOGRAFI YANG DI-REPOSTING TANPA IZIN PENCIPTA DALAM YOUTUBE BERDASARKAN UUHC - Tamara Sindytia; Rakhmita Desmayanti (Reformasi Hukum Trisakti, 2021)
Copyright is an exclusive right owned by the creator that arises automatically based on the declarative principle after a creation is realized in a tangible form. In the Copyright law, one of the creations that are protected is Cinematographic Works contained in article 40 paragraph 1 letter M. Cinematographic works are creations in the form of moving images like video content contained on YouTube. This study uses a method with the type of normative legal research that is descriptive in nature and also primary data to support secondary data by conducting interviews with the parties concerned and this research is analyzed qualitatively. The conclusion of this study is that the act of reposting cinematographic works is a form of violation of economic rights and moral rights in which efforts that creators can take to avoid reposting are to turn on the content ID feature that has been provided by Youtube in this case to identify videos that have something in common with the creator. may register with the Directorate General of Intellectual Property as evidence in the event of a Copyright dispute and join the Collective Management Institute for the management of economic.